2005
DOI: 10.1051/0004-6361:20041865
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic outflows from remnants of compact object mergers and their viability for short gamma-ray bursts

Abstract: Abstract. We present the first general relativistic hydrodynamic models of the launch and evolution of relativistic jets and winds, driven by thermal energy deposition, possibly due to neutrino-antineutrino annihilation, in the close vicinity of black hole-accretion torus systems. The latter are considered to be the remnants of compact object mergers. Our two-dimensional simulations establish the link between models of such mergers and future observations of short gamma-ray bursts by the SWIFT satellite. They … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
296
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(316 citation statements)
references
References 64 publications
18
296
2
Order By: Relevance
“…The physical mechanisms behind launching such a burst are still far from being settled, it seems, [61,62]. As discussed previously, the emerging neutrino-driven winds pose a serious threat to the emergence of an ultra-relativistic outflow, and therefore not every NSNS merger may actually be able to produce an SGRB.…”
Section: (E) Electromagnetic Transientsmentioning
confidence: 99%
“…The physical mechanisms behind launching such a burst are still far from being settled, it seems, [61,62]. As discussed previously, the emerging neutrino-driven winds pose a serious threat to the emergence of an ultra-relativistic outflow, and therefore not every NSNS merger may actually be able to produce an SGRB.…”
Section: (E) Electromagnetic Transientsmentioning
confidence: 99%
“…The central engine timescale (the accretion timescale in our example; Zhang et al 2009) can be constrained to be at most the observed duration or t acc 1 s (Aloy et al 2005). This constraint will carve out a region in Figure 2 to the left of the t acc =1 s or R out =2.3×10 8 cm line.…”
Section: Generic Blandford-znajek Scenariomentioning
confidence: 99%
“…Aloy et al [71] simulate the propagation of jets powered by energy input along the rotation axis (as would be supplied by the νν annihilation). They find that if the half-opening angle of the energy injection region is moderately small ( < ∼ 45 • ) and the baryon density around the black hole is sufficiently low, jets with the Lorentz factors in the hundreds can be produced given an energy input L νν ≈ 10 49 -10 50 ergs/s lasting ∼ 100 ms.…”
Section: Implication To Sgrbsmentioning
confidence: 99%